ANALISIS KINERJA KEUANGAN DAERAH TERHADAP INDEKS PEMBANGUNAN MANUSIA PADA PEMERINTAH DAERAH KABUPATEN DAN KOTA DI PROVINSI JAWA BARAT - Gian Riksa Wibawa; Arif Arif (LP2M Universitas Perjuangan Tasikmalaya, 2021)
The purpose of this study is to analyze the regional financial performance (degree of decentralization ratio, regional financial dependency ratio, regional financial independence ratio) of districts/cities in West Java. And to see the effect, either simultaneously or partially on the Human Development Index. Using panel data, namely time series from 2016-2020 as well as cross section data of 18 districts and 9 cities in West Java. Using panel data regression analysis method. The findings of the analysis show that districts/cities in West Java still have relatively low regional financial performance. Panel data regression analysis using the Fixed Effect Model (FEM) method reveals that regional financial performance simultaneously has a significant effect on the HumanDevelopment Index, and partially degree of decentralization ratio has a positive and significant effect on the Human Development Index, regional financial dependency ratio and regional financial independence ratio have a negative and significant impact on the Human Development Index.